PREVENTING SCHOOL BULLYING DENGAN MEDIA CD - Agus Basuki (MAJALAH ILMIAH PEMBELAJARAN, 2010)
The goal of the article is giving the understanding of bullying attitude happenend in school. The attitude mostly done by teneger counsicusly or uncounsculy arrund them.The forms os school bullying such us direct contac, direct verbal contac, non verbal attitude, sexual harassment and others.The prevention effort can be done by applying interactive Media. One of them media interactive is CD. By running this program, involving all the elements in school, parents, teachers, staff, and school community the involve in this program.